Long Noncoding RNA (lncRNA) HOTAIR Affects Tumorigenesis and Metastasis of Non-Small Cell Lung Cancer by Upregulating miR-613 - Jiang, Caiyu (Oncol Res, 2018)
Non-small cell lung cancer (NSCLC) is one of the most deadly cancers with poor prognosis. Recent findings suggested that the lncRNA HOTAIR played an important role in tumorigenesis and metastasis. In the present study, HOTAIR was highly expressed in NSCLC tumor tissues and cell lines (H1299, H23, H292, and A549). Downregulation of HOTAIR suppressed cell proliferation and invasion, while it promoted apoptosis of NSCLC cells. The targeting relationship between HOTAIR and miR-613 was first revealed by bioinformatics prediction. miR-613 was found to be lowly expressed in NSCLC tumor tissues and cell lines. Knockdown of HOTAIR increased the expression of miR-613 significantly, and cotransfection with miR-613 inhibitor reversed this increase, indicating that the expression of miR-613 was negatively regulated by HOTAIR. The targeting relationship between HOTAIR and miR-613 was further confirmed through the luciferase report assay. Moreover, the cotransfection of HOTAIR shRNA and miR-613 inhibitor counteracted the tumor inhibition effects of HOTAIR shRNA through promoting cell proliferation and invasion while suppressing apoptosis in NSCLC cells, suggesting that the HOTAIR/miR-613 axis was involved in tumorigenesis and metastasis of NSCLC. In vivo experiments revealed that knockdown of HOTAIR decreased tumor growth and invasion and increased apoptosis and miR-613 expression. In conclusion, our study indicated that downregulation of HOTAIR suppressed tumorigenesis and metastasis of NSCLC via upregulating the expression of miR-613. The HOTAIR/miR-613 axis might provide a new potential therapeutic strategy for NSCLC treatment.